Introduction to modern EW systems - De Martino, Andrea (Artech House radar library, 2012)
Master the latest electronic warfare (EW) techniques and technologies related to on-board military platforms with this authoritative resource. You gain expert design guidance on technologies and equipment used to detect and identify emitter threats, giving you an advantage in the never-ending chess game between sensor guided weapons and EW systems. This unique book offers you deeper insight into EW systems principles of operation and their mathematical descriptions, arming you with better knowledge for your specific design applications. Moreover, you get practical information on how to counter.